2021
DOI: 10.1039/d1ce00451d
|View full text |Cite
|
Sign up to set email alerts
|

Variable stoichiometry cocrystals: occurrence and significance

Abstract: The occurrence of variable stoichiometry cocrystals offers the prospect to acquire more solid forms of the same system. The control of stoichiometry is extremely important concerning the purity and intellectual...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 133 publications
0
22
0
Order By: Relevance
“…269 Disparities in the hydrogen bond donor and acceptor ratio, awkward shape, larger molecular structure, competition between hydrogen bonding groups, and packing frustration are the main reasons for multiple stoichiometry and/or incorporation of guest/solvent/water molecules to complete the hydrogenbonding pairing for maximum packing efficiency and adjustment of crystal symmetry. 270 The existence of variable stoichiometry cocrystals offer additional solid forms of a drug for property management and intellectual property space. Dicarboxylic acids are common coformers for multiple stoichiometry cocrystals or salts.…”
Section: Ternary and Higher-order Cocrystalsmentioning
confidence: 99%
“…269 Disparities in the hydrogen bond donor and acceptor ratio, awkward shape, larger molecular structure, competition between hydrogen bonding groups, and packing frustration are the main reasons for multiple stoichiometry and/or incorporation of guest/solvent/water molecules to complete the hydrogenbonding pairing for maximum packing efficiency and adjustment of crystal symmetry. 270 The existence of variable stoichiometry cocrystals offer additional solid forms of a drug for property management and intellectual property space. Dicarboxylic acids are common coformers for multiple stoichiometry cocrystals or salts.…”
Section: Ternary and Higher-order Cocrystalsmentioning
confidence: 99%
“…The synthesis of cocrystal and/or salt relies on the intermolecular interactions, explicitly the directional hydrogen bonds between solute···solute and solute···solvent. Thus, the rational multicomponent crystal design with desirable properties is centered on the expected supramolecular interactions. Stability, solubility, and membrane permeation are a few fundamental prerequisites in the development of a drug to achieve maximum efficacy . Molecular salt formulation is a proven technology to modify drug pharmacokinetic properties, and over 50% of drug compounds in the market are administered in salt formulations treasured today. The only limitation is that it only works for drug candidates with an ionizable functional group.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the formation of cocrystals by solid-state grinding followed by solution growth techniques is common, , while many are selectively prepared only by solid-state grinding or solution growth . To understand the mechanism of formation and/or the kinetics of cocrystallization, it is imperative to understand the various factors that can affect the (i) stability and (ii) phase transformations of the product cocrystals. , Reports are available demonstrating the role of solution chemistry, mechanochemical methods, and conformer stoichiometric ratio , in the cocrystallization of different stoichiometric cocrystals. Sarma et al reported the role of π-stacking interactions and hydrogen bond synthons in the alteration of cocrystal stoichiometries .…”
Section: Introductionmentioning
confidence: 99%